2019
DOI: 10.1139/cjz-2018-0210
|View full text |Cite
|
Sign up to set email alerts
|

Non-digestible proteins and protease inhibitors: implications for defense of the colored eggs of the freshwater apple snailPomacea canaliculata

Abstract: Apple snails (Pomacea Perry, 1810) are successful invaders that cause ecological perturbations, economic losses, and medical issues. A peculiar trait of this snail is a high biological potential, related to the absence of predators of their eggs. Eggs show protease inhibitor (PI) activity, originally ascribed to PcOvo perivitellin in the apple snail Pomacea canaliculata (Lamarck, 1822) but absent in PmPV1, the orthologoue of PcOvo, in eggs of the apple snail Pomacea maculata Perry, 1810. As egg fluid diminishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
0
13
0
3
Order By: Relevance
“…Among the orthogroups, 13 were found in all of the four ampullariids, including five PV1 subunits, five immune‐responsive proteins (C1q domain‐containing protein, CD109 antigen, deleted in malignant brain tumors 1, tachylectin‐related protein and soma ferritin), and three other proteins (superoxide dismutase 1, apoptosis‐inducing factor and novel protein). Interestingly, two orthogroups, CaBP that is involved in forming the egg shell, and Kunitz/Bovine pancreatic trypsin inhibitor that inhibits the functioning of multiple digestive proteases, were only detected in the three species of Pomacea. The presence of multiple immunoproteins in the PVF of the four species may indicate their role in defense against pathogens, as has been suggested for the eggs of the pulmonate snail Biomphalaria glabrata .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the orthogroups, 13 were found in all of the four ampullariids, including five PV1 subunits, five immune‐responsive proteins (C1q domain‐containing protein, CD109 antigen, deleted in malignant brain tumors 1, tachylectin‐related protein and soma ferritin), and three other proteins (superoxide dismutase 1, apoptosis‐inducing factor and novel protein). Interestingly, two orthogroups, CaBP that is involved in forming the egg shell, and Kunitz/Bovine pancreatic trypsin inhibitor that inhibits the functioning of multiple digestive proteases, were only detected in the three species of Pomacea. The presence of multiple immunoproteins in the PVF of the four species may indicate their role in defense against pathogens, as has been suggested for the eggs of the pulmonate snail Biomphalaria glabrata .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, P. diffusa and M. cornuarietis invest more on immune proteins and protease inhibitors. The three Pomacea species have a unique CaBP required for the formation of the calcareous shell of terrestrial eggs, and a Kunitz/Bovine pancreatic trypsin inhibitor that, at least in P. canaliculata and P. maculate , inhibit multiple digestive proteases of mice . In addition, duplication and positive selection of the CaBP and PV2 subunits were likely responsible for the aerial egg deposition and the evolution of the PV2 toxic protein as an anti‐predation mechanism in P. canaliculata and P. maculata .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PdPV1 is composed by six polypeptide chains similar to its orthologs PcOvo, PsSC and PmPV1 (Pasquevich et al, 2017;Ituarte et al, 2018Ituarte et al, , 2019 with only moderate sequence similarities among them. It has been suggested that they were generated by an ancient gene duplication (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PdPV1 is composed by six polypeptide chains similar to its orthologs PcOvo, PsSC and PmPV1 (Pasquevich et al ., 2017; Ituarte et al ., 2018, 2019) with only moderate sequence similarities among them. It has been suggested that they were generated by an ancient gene duplication (Sun et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%